1986
DOI: 10.1038/319600a0
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive transient rises in cytoplasmic free calcium in hormone-stimulated hepatocytes

Abstract: In the stressed animal, the vasoactive hormones vasopressin and angiotensin-II and the neurotransmitter noradrenaline induce liver cells to release glucose from glycogen. The intracellular signal that links the cell-surface receptors for noradrenaline (alpha 1) and vasoactive peptides to activation of glycogenolysis is known to be a rise in the cytoplasmic concentration of free calcium ions (free Ca). The receptors for these agonists induce the hydrolysis of phosphatidylinositol 4,5-bisphosphate, a minor plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
414
0

Year Published

1988
1988
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 768 publications
(440 citation statements)
references
References 25 publications
26
414
0
Order By: Relevance
“…The failure to detect such prolonged oscillations lies probably on the fact that not all acini are oscillating synchronously and, therefore, the average change in [Ca2+]i of the total population may well be hidden within the noise of the recorded trace. This behaviour of pancreatic acini is in keeping with the presence of agonist-induced [Ca2+]i oscillations documented in other cell types [26][27][28].…”
Section: Resultssupporting
confidence: 84%
“…The failure to detect such prolonged oscillations lies probably on the fact that not all acini are oscillating synchronously and, therefore, the average change in [Ca2+]i of the total population may well be hidden within the noise of the recorded trace. This behaviour of pancreatic acini is in keeping with the presence of agonist-induced [Ca2+]i oscillations documented in other cell types [26][27][28].…”
Section: Resultssupporting
confidence: 84%
“…(2) Glucagon alone is also able to induce an increase in intracellular [Ca2+]. However, the time of onset lags by some 10 s and the rapidity and magnitude of the change are not quite as great (Charest et al, 1983; see also Mauger and Claret, 1986 Studies on single hepatocytes (see, e.g., Woods et al, 1986Woods et al, , 1987 have shown that Ca2+-mobilizing hormones induce oscillations in intracellular Ca2 , the frequency of which depends on the agonist concentration. It is of interest that in this single-cell system the responses to vasopressin are different from those to phenylephrine , as in the intact perfused rat liver (Altin and Bygrave, 1985; see Figure 1).…”
Section: Studies On Ca2`fluxes In Hepatocytes Induced By Ca2+-mobilizmentioning
confidence: 99%
“…Since the 1980s, when self-sustained calcium oscillations were first discovered [1,2] numerous further experimental observations have been published (for review, see [3][4][5]). …”
Section: Introductionmentioning
confidence: 99%